Elastocaloric effects in the extreme. (15th April 2018) - Sehitoglu, H.; Wu, Y.; Ertekin, E.
Abstract: There is a resurgence of interest in the elastocaloric (EC) effect of shape memory alloys (SMAs). The temperature change associated with the EC effect can be substantial, far exceeding those observed in well-known electrocaloric and magnetocaloric materials. The major driver of the EC effect is the entropy change of transformation. Historically the EC effect under superelasticity has been studied at mainly 25 °C. The current paper considers six SMAs across a variety of test temperatures, focusing not only on the EC cooling capability but also on three important factors for practical application: the role of stress/thermal hysteresis, Md temperature, and fatigue.